2014
DOI: 10.1002/jctb.4513
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic surface treatment of poly (3‐hydroxybutyrate) (PHB), and poly (3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV)

Abstract: BACKGROUND: Polyhydroxyalkanoates (PHA) are very interesting biopolymers, their most promising applications lie in biomedical science. The wettability of the surface of PHA increases their biocompatibility properties, making them suitable for such applications. RESULTS: The treatment of the surface of poly (3-hydroxybutyrate) (PHB) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate)(PHBV) films with the cutinase TfCut2 from Thermobifida fusca KW3 resulted in decrease of the water contact angle of PHB films from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…YP1, which could cause obvious damage to PE film, including pits and cavities on the surface. Berezina et al (2015) reported that PHB film treated with the cutinase TfCut2 showed a rough surface compared to the untreated control, suggesting a degradation of the outermost surface layers of the film. In this study, although the degradation of PET by strain WL-3 was observed using SEM, the degradation ability was not determined quantitatively.…”
Section: Surface Treatment Of Pet Film Using Strain Wl-3mentioning
confidence: 99%
“…YP1, which could cause obvious damage to PE film, including pits and cavities on the surface. Berezina et al (2015) reported that PHB film treated with the cutinase TfCut2 showed a rough surface compared to the untreated control, suggesting a degradation of the outermost surface layers of the film. In this study, although the degradation of PET by strain WL-3 was observed using SEM, the degradation ability was not determined quantitatively.…”
Section: Surface Treatment Of Pet Film Using Strain Wl-3mentioning
confidence: 99%
“…However, certain applications require less brittle, more elastic polymer with lower glass transition temperature (T g ). This can be achieved by modulation of PHB composition and the incorporation of the 3-hydroxyvalerate (3-HV) monomeric units [16,17].…”
mentioning
confidence: 99%